SOSIALISASI DAN EDUKASI PEMILAHAN SAMPAH PADA MASYARAKAT SEKITAR PARKIR BUS PARIWISATA SUNAN BONANG, TUBAN - muhammad sudrajat (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
The problem of waste is becoming increasingly complex due to limited space for processing waste, incompatibility in spatial planning, lack of waste processing facilities, low public knowledge regarding waste processing, the large number of land conversions for housing, and the rapid increase population in the Tuban Regency. This community service activity was carried out at the location of the religious tourism bus parking of the Sunan Bonang Tomb. Garbage scattered at the parking location comes from bus passengers who do not have the awareness to throw garbage in its place. In addition, the other main sources of waste come from traders at tourist parking locations and pedicab drivers. This condition is mostly caused by the low of knowledge and awareness of the community regarding waste and its processing. This education and socialization of waste sorting is carried out to traders, visitors and pedicab drivers around the bus parking location. In this activity, the majority of traders have good knowledge regarding waste sorting into organic and inorganic waste, while for pedicab drivers, the majority do not have good knowledge regarding waste sorting. It is hoped that in the future this community service activity can be carried out in a sustainable manner, so that later the waste at the bus parking location can be used into something useful